تعليم مهارة الكلام بالأنشطة اللغوية في معهد والي صاعا عابر فونوروكو - Aminah, Siti (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ملخص تعتبر مهارات التحدث من أهم المهارات في تطوير اللغة العربية. بتعيلم مهارة الكلام، يمكن لأي شخص أن ينقل ما يدور في ذهنه. الأنشطة اللغوية هي إحدى استراتيجيات التعليم لمهارة الكلام. الأنشطة اللغوية هي أنشطة يتم تنفيذها خارج الفصل الدراسي وهي أنشطة غير رسمية .ولكل المعهد أنشطة لغوية متنوعة ومختلفة وفي تنفيذها اختلاف أيضا. من المشاكل المذكورة، تصف الباحثة استراتيجية تعليم مهارة الكلام بالأنشطة اللغوية في معهد والي صاعا عابر فونوروكو. ومنهجية البحث هي منهج كيفي بالمدخل الوصفي. ونتائج البحث هي أن أشكال الأنشطة اللغوية لتعليم مهارة الكلام في معهد والي صاعا عابر فونوروكو تتكون من إلقاء المفردات والمحادثة والمحاضرة. ABSTRAK Speaking skills are one of te most important skills in the development of the Arabic language. With speaking skill’s learning, a person can convery what is on his mind. One of speaking skill’s learning strategies is through language activities. Language activities are carried out outside the classroom that are non-formal. Each Islamic boarding school has various and different language activities and the implementation is also different. From the problems above, the researcher tries to review speaking skill’s learning strategies through language activities at the Wali Songo Islamic Boarding School Ngabar Ponorogo. The approachused is a qualitative approach and descriptive research type. The result of this research is that the forms of language activities for speaking skill’s learning are the provision of vocabularies, conversation and speeches.